Evaluation and development opportunities of the disused Lutheran cemeteries within the Maskulińskie and Pisz Forest Divisions for thanatourism - Sobotka, Sławomir; Długozima, Anna (Turyzm/Tourism, 2015)
This paper presents the results of a study of 67 disused Lutheran cemeteries situated in the Pisz and Maskulińskie Forest Divisions (the southern part of Warmińsko-Mazurskie Province). An inventory of gravestones and vegetation was compiled, and the types, sizes and geographical coordinates of the cemeteries were determined using a GPS receiver. The paper also presents an evaluation of the cemeteries, illustrated through examples in the Maskulińskie Forest Division. The best preserved and/or most interesting cemeteries are going to be included on a tourism trail.